Karakteristik Pelumas Bekas Hasil Adsorpsi Menggunakan Arang Batang Kesambi (Schleichera oleosa) dan Zeolit Alam Ende Teraktivasi H3PO4 - Cunha, Theodorus M. Da; Fone, Maria Y.B.; Tawa, Bibiana Dho; Ola, Antonius R. B. (Universitas Nusa Cendana, 2022)
Used lubricants contain contaminants from oxidation and thermal degradation, resulting in a decrease in the quality and performance of the lubricant. Therefore, the adsorption process is carried out using kesambi stem charcoal and natural zeolite Ende activated H3PO4 to remove contaminants and improve the quality of used lubricants. Determination of the density and kinematic viscosity of used lubricants mass variations of 0.5, 0.66, 1 and 2 grams for each adsorbent. The results obtained show that the value of the used lubricant density from the adsorption results is relatively the same, namely 0.83 g/cm3, while the kinematic viscosity is different for each variation of the mass and type of adsorbent. Kesambi stem active charcoal has an optimum mass of 0.66 grams with a kinematic viscosity value of 128.84 cSt, active natural zeolite at a mass of 0.5 grams of 113.59 cSt and continued use of active natural zeolite-active natural charcoal, namely at a mass of 2 grams of 106, 38 cSt. These results indicate that the variation in the mass of the adsorbent has no effect on the change in density value but shows a significant change in the increase in the value of the kinematic viscosity of the used lubricant from the adsorption. The best percentage of kinematic viscosity increase efficiency is using activated charocoal, which is 71.83%.